2004
DOI: 10.1017/s0952523804216054
|View full text |Cite
|
Sign up to set email alerts
|

Development of sensitivity to visual motion in macaque monkeys

Abstract: The development of spatial vision is relatively well documented in human and nonhuman primates. However, little is known about the development of sensitivity to motion. We measured the development of sensitivity to direction of motion, and the relationship between motion and contrast sensitivity in macaque monkeys as a function of age. Monkeys (Macaca nemestrina, aged between 10 days and 3 years) discriminated direction of motion in random-dot kinematograms. The youngest monkeys showed directionally selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
85
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 50 publications
7
85
4
Order By: Relevance
“…In addition, from the earliest age studied, the PIm relay cells were cFosϩ/visually driven. Given the observation that in marmosets and macaques there was a capacity to detect motion soon after birth (Kiorpes and Movshon, 2004;Izumi et al, 2011), we have identified PIm input as likely driving this perceptual capability in early life.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In addition, from the earliest age studied, the PIm relay cells were cFosϩ/visually driven. Given the observation that in marmosets and macaques there was a capacity to detect motion soon after birth (Kiorpes and Movshon, 2004;Izumi et al, 2011), we have identified PIm input as likely driving this perceptual capability in early life.…”
Section: Discussionmentioning
confidence: 69%
“…Behavioral studies have demonstrated the capacity for both macaques and marmosets to detect motion within the first month after birth (Kiorpes and Movshon, 2004;Izumi et al, 2011), and humans have the ability to discriminate direction of motion relatively early in visual development (Banton et al, 2001). Previous electrophysiological recordings from Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, binocularly discordant signals early in life dramatically alter visual cortical functions (1,2). For example, early ocular misalignment (strabismus) that disrupts binocular image matching results in a drastic reduction in the proportion of V1 neurons that can be activated by monocular stimulation of either eye (3)(4)(5)(6).…”
mentioning
confidence: 99%